Global burden and trends of multiple myeloma attributable to high body mass index: a comprehensive analysis of the global burden of disease 2021 study with projections to 2040 - Yue Xie; Jing Li; Jingwen Yu; Jun Zhang; Jian Guo (BMC Public Health)
Abstract Background Obesity and overweight are increasingly recognized as significant risk factors for the incidence and progression of Multiple Myeloma (MM). However, its epidemiological investigation including the disease burden and its trends remains insufficiently explored. Objective This study aims to examine the burden and temporal trends of MM attributable to high body mass index (BMI), focusing on variations by age, sex, Socio-demographic Index (SDI), and geographic region. Methods Data on MM cases linked to high BMI were obtained from the Global Burden of Disease (GBD) 2019 study, including deaths, disability-adjusted life-years (DALYs), and their age-standardized rates. Temporal trends in mortality were analyzed, and the relationships between SDI, standardized exposure value (SEV), and MM burden were assessed using Pearson correlation analysis. Results Between 1990 and 2021, MM deaths due to high BMI increased from 3.00 thousand to 9.20 thousand, while DALYs rose from 72.00 thousand to 207.60 thousand. The age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) showed annual percentage increases of 0.91% and 0.94%, respectively. The highest burden was observed in high-SDI regions, though the most rapid growth occurred in lower-SDI areas. Western Europe and North America had the greatest disease burden, with males exhibiting consistently higher ASMR and ASDR than females. The oldest age groups (90–94 and 95 + years) were most affected. Strong positive correlations were found between MM burden and both SDI and SEV at regional and national levels. Future projections indicate a continued rise in deaths and DALYs by 2040. Conclusion The growing impact of high BMI on MM, particularly in developed regions, highlights the need for targeted public health strategies to mitigate its effects. Increasing awareness and preventive measures are crucial to reducing the disease burden associated with high BMI.